(untitled) (Revista Direitos Humanos e Democracia, 2021)
This article aims to understand the debate regarding the practice known as indigenous "infanticide", focusing on the making of the Bill nº 1.057/2007, that creates ways to fight against its practice. To do so, we carried out a documentary research, seeking to put in evidence the connexions between the assumptions made, their factual basis and the changes performed at the bill. Lastly, we analyzed the results using the theories of Legisprudence (Wintgens) and of the Critical Theory of Human Rights (Herrera Flores, Costas Douzinas). The study concluded that the debate obliterated all the possibilities but the legislative way, ignored the lack of data capable of giving support to the bill and had an uncomplying stance that turned the effective participation of those affected by it harder.